2020
DOI: 10.1103/physrevlett.124.155301
|View full text |Cite
|
Sign up to set email alerts
|

Fully Coupled Two-Fluid Dynamics in Superfluid He4 : Anomalous Anisotropic Velocity Fluctuations in Counterflow

Abstract: We investigate the thermal counterflow of the superfluid 4 He by numerically simulating threedimensional fully coupled dynamics of the two fluids, namely quantized vortices and a normal fluid. We analyze the velocity fluctuations of the laminar normal fluid arising from the mutual friction with the quantum turbulence of the superfluid component. The streamwise fluctuations exhibit higher intensity and longer-range autocorrelation, as compared to transverse fluctuations. Those anomalous fluctuations are consist… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 66 publications
(105 reference statements)
2
37
0
Order By: Relevance
“…Microscopically, this assumption does not hold. Recent studies [31][32][33][34] have shown that the normal fluid profile is nontrivially modulated by the presence of quantized vortices, through mutual friction on the scale of the intervortex distance. However, in the analysis below, we consider only the macroscopic vortex bundle structure that develops in the macroscopic steady normal flow; a study of the characteristic small-scale structures that emerge due to coupled dynamics remains future work to be dealt with.…”
Section: Bundle Formation In Region IImentioning
confidence: 99%
“…Microscopically, this assumption does not hold. Recent studies [31][32][33][34] have shown that the normal fluid profile is nontrivially modulated by the presence of quantized vortices, through mutual friction on the scale of the intervortex distance. However, in the analysis below, we consider only the macroscopic vortex bundle structure that develops in the macroscopic steady normal flow; a study of the characteristic small-scale structures that emerge due to coupled dynamics remains future work to be dealt with.…”
Section: Bundle Formation In Region IImentioning
confidence: 99%
“…2000; Yui et al. 2020), in the close proximity of moving quantized vortices. However, these wake structures were observed at relatively small fluid velocities, that is, their topology in dense vortex tangles, which are specifically relevant for the present study, is currently unknown.…”
Section: Resultsmentioning
confidence: 99%
“…This might be related once more to the relatively small size of the data sets collected in the past and/or to the fact that these studies were performed at relatively small heat fluxes (Yui et al. 2020).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations